Special self-cleaning ABS (Acrylonitrile Butadiene Styrene) composite modified material for grater and preparation method thereof
By adding and efficiently dispersing glass fibers and nanomaterials in the ABS grater, self-cleaning ABS composite modified materials are prepared, which solves the problem of adsorbing oil stains and bacterial growth of the ABS grater, and improves the material's aging resistance and self-cleaning properties.
Patent Information
- Application Number
- CN202411828917.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-21
AI Technical Summary
During use, ABS graters are prone to adsorbing stubborn oil and bacteria, and long-term exposure to light will cause yellowing and darkening color.
A self-cleaning ABS composite modified material was prepared by adding glass fiber, nano SiO2, nano TiO2, nano ZnO and other materials to the ABS resin and performing efficient dispersion treatment. This material ensures good dispersion of the nanomaterial in ABS resin by pre-grinding dispersed nanomaterials in high glue powder, thereby improving the hydrophobic and oleophobic properties of the material.
The self-cleaning and hydrophobic properties of the ABS grater surface are realized, effectively preventing oil stains from adhesion and bacterial growth, and at the same time improving the aging resistance of the material and preventing yellowing.
Smart Images

Figure CN119661971A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of functional modified plastics, and more specifically to a self-cleaning ABS composite modified material specially used for graters and a preparation method thereof. Background Art
[0002] ABS resin is a terpolymer made by copolymerization of acrylonitrile, butadiene and styrene. ABS resin has high strength, toughness and hardness, and can withstand wear and impact in daily use. It is easy to be molded by injection molding and is suitable for making plastic products of various shapes and structures.
[0003] Graters are commonly used in the kitchen for cutting. Various vegetables can be easily cut into thin slices, filaments and other ingredients through graters, which greatly saves the time of cutting vegetables and improves cooking efficiency, becoming an indispensable kitchen utensil. At present, the main material of the grater is ABS resin, which has good resistance to acids, alkalis and salts, and has a high surface finish after processing. Compared with polypropylene (PP) and polyethylene (PE), graters made of ABS have better stability, rigidity and texture.
[0004] However, when ABS graters are exposed to light, the butadiene rubber in them will gradually change color, so the color of the product will turn yellow and darker after a period of use. In addition, the current high-end graters are also designed with food receiving boxes, which are in contact with various vegetables and easily absorb and adhere to oil stains in the kitchen, accumulating into dirt that is difficult to clean, making it difficult to clean and extremely easy to breed bacteria.
[0005] The special size structure of nanomaterials can make the surface of the material hydrophobic and oleophobic. In order to effectively prevent ABS materials from adhering to oil stains, it has been reported that by applying nano coatings on the surface of ABS plastic products, the hydrophobic and oleophobic properties can be increased, thereby preventing oil stains from adhering. For example, nano silica coatings can increase the oil and dirt resistance of ABS plastic surfaces. However, the thickness of the nano coating is very thin, it is easy to be damaged and fall off, and the wear resistance and scratch resistance are poor. In addition, nano coatings use organic solvents, there is a risk of releasing VOCs, and are not suitable for direct contact with food.
[0006] In the field of polymer modification technology, the preparation process of self-cleaning plastics can be greatly simplified by dispersing nanomaterials in ABS. However, nanomaterials refer to materials with a particle size between 1 and 100 nanometers, which are much smaller than ordinary particles. When nanomaterials are added to plastics, they are very easy to agglomerate due to their small size, resulting in poor dispersibility and difficulty in achieving the hydrophobic and oleophobic functions of nano-sized structural materials.
[0007] This application is proposed based on the dispersion problem of existing nanomaterials in ABS resin. Through the efficient dispersion of nanomaterials in ABS resin, the self-cleaning properties of the nanomaterials such as hydrophobic and oleophobic properties and ultraviolet shielding properties are brought into play, and a self-cleaning ABS composite modified material that can meet the needs of graters is developed. Summary of the invention
[0008] In view of the problems that ABS kitchen graters easily absorb stubborn oil stains, become soaked and breed bacteria, and are prone to yellowing and discoloration after long-term use, the present application provides a self-cleaning ABS composite modified material specifically for graters; further, a preparation method of the self-cleaning ABS composite modified material is provided.
[0009] The first object of the present invention is to provide a self-cleaning ABS composite modified material for graters, which is characterized by comprising the following raw material components by weight: 50-65 parts of ABS resin, 15-25 parts of glass fiber, 6-8 parts of ABS high-glue powder, 5-8 parts of MBS resin, 5-6 parts of precipitated barium sulfate, 3-4 parts of polytetrafluoroethylene powder, 2-3 parts of nano-SiO2, 1-2 parts of nano-TiO2, 1-2 parts of nano-ZnO, 0.5-1.5 parts of auxiliary compatibilizer, 0.5-0.8 parts of anti-glass fiber exposure agent, 0.3-0.5 parts of silicone masterbatch, 0.3-0.5 parts of antioxidant, and 0-2 parts of masterbatch; The precipitated barium sulfate, polytetrafluoroethylene powder, nano-SiO2, nano-TiO2, nano-ZnO and anti-glass fiber exposure agent are ground and pre-dispersed in ABS high-rubber powder before use.
[0010] Preferably, the glass fiber is an alkali-free continuous glass fiber or an alkali-free chopped glass fiber pre-impregnated with a silane coupling agent; and the fiber diameter is ≤13 μm.
[0011] Preferably, the particle size of the ABS high-rubber powder is ≤50μm; the content of butadiene is 68-70%; the ABS high-rubber powder has good melt fluidity and is easy to process and disperse. When used, it can be quickly melted and evenly dispersed in ABS. By pre-dispersing the nanomaterial in the ABS high-rubber powder, the nanomaterial is well dispersed in the ABS resin. The excellently dispersed nanomaterial makes the surface of the ABS plastic product have a certain degree of nano-scale structure, thereby having hydrophobic and oleophobic properties.
[0012] Preferably, the mass proportion of methyl methacrylate in the MBS is 65-70%; MBS is a ternary graft polymer prepared by emulsion graft polymerization of methyl methacrylate, butadiene and styrene, and has good compatibility with ABS; at the same time, M refers to methyl methacrylate, M has polarity, and a higher proportion of M promotes the compatibility of glass fiber, precipitated barium sulfate, polytetrafluoroethylene powder, nano-SiO2, nano-TiO2 and ABS; further, the use of MBS resin will enhance the gloss of the material.
[0013] Preferably, the particle size of the precipitated barium sulfate D50 is 1.5-2 μm; the precipitated barium sulfate not only provides high gloss and stable hue, which is beneficial for color matching, but also can improve the processing fluidity of material injection molding and enhance the dimensional stability of the injection molding grater.
[0014] Preferably, the particle size of the polytetrafluoroethylene powder D50 is 2-10 μm; the bond between the fluorine atom and the carbon atom in the polytetrafluoroethylene molecule is a polar bond, which makes the polytetrafluoroethylene highly hydrophobic; at the same time, the electronegativity of the fluorine atom is much higher than that of the carbon atom, which makes the polytetrafluoroethylene molecule have a certain electronegativity. Through good dispersion, the polytetrafluoroethylene exhibits anti-adhesion when in contact with oil esters, thereby achieving an oleophobic effect. Preferably, the nano-SiO2 is gas-phase nano-SiO2; nano-SiO2 dispersed in ABS can effectively improve the aging resistance of the product, keep the color of the plastic product unchanged for a long time, and improve the surface density, smoothness and self-cleaning performance of the product.
[0015] Preferably, the nano-TiO2 is anatase nano-TiO2; anatase nano-TiO2 has excellent photocatalytic properties and can continuously generate free radicals with strong oxidizing properties under the action of light, thereby killing bacteria. This antibacterial property enables ABS products containing anatase nano-TiO2 to effectively inhibit bacterial growth. Furthermore, anatase nano-TiO2 has a strong ultraviolet shielding ability, which can better prevent aging and yellowing of ABS, and avoid the problem of yellowing caused by redox reactions when using silver-based antibacterial agents.
[0016] Preferably, the nano ZnO is nano-scale ultrafine active ZnO with a D50 particle size of 50-100 nm prepared by wet chemical NPP method. It can well shield ultraviolet rays and prevent ABS from yellowing and discoloration; it has good photocatalytic activity. Under light irradiation, the nano ZnO can decompose negatively charged electrons and positively charged holes by itself, thereby stimulating oxygen in the air to become active oxygen, and undergoing oxidation reactions with various microorganisms, thereby killing bacteria.
[0017] Preferably, the auxiliary compatibilizer is a silane coupling agent; for example, vinyl trimethoxy silane with the brand name A171, γ-(2,3-epoxypropoxy)propyl trimethoxy silane with the brand name KH-560, and γ-mercaptopropyl trimethoxy silane with the brand name KH-580.
[0018] Preferably, the anti-glass fiber exposure agent is ethylene bis fatty acid amide (EBS) or commercial anti-glass fiber exposure agent TAF; the anti-glass fiber exposure agent will enhance the dispersion of glass fiber in ABS, prevent the glass fiber reinforcement from being exposed, and improve the surface finish of the grater product.
[0019] Preferably, the antioxidant is at least one of the antioxidant BHT, the antioxidant DSTDP, and the antioxidant 1076.
[0020] Preferably, the masterbatch is added according to the color requirement. When porcelain white material is required, no masterbatch is needed. On the basis of porcelain white as the basic color, in order to ensure the stability of other colors and the bright effect of the grater, a masterbatch with ABS as the carrier is preferred.
[0021] The second object of the present invention is to provide a method for preparing a self-cleaning ABS composite modified material for a grater, and the specific method is as follows: S1. Weigh the fine powder raw materials ABS high rubber powder, precipitated barium sulfate, polytetrafluoroethylene powder, nano-SiO2, nano-TiO2, nano-ZnO, and anti-glass fiber exposure agent according to weight, add them to the vertical stirred mill, grind, disperse and refine them with zirconium balls as the dispersing grinding medium; then screen out the zirconium balls, add antioxidants and liquid auxiliary compatibilizers, mix them evenly, and send them to 1# silo for standby use; S2 weighed in parts by weight granular raw materials ABS resin, MBS resin, silicone masterbatch, masterbatch, added to a high-speed mixer for high-speed dispersion mixing, and sent to 2 # silo standby; S3. Use a loss-in-weight scale to automatically weigh and measure the materials in 1# silo and 2# silo, mix them, and feed them into the hopper of a parallel twin-screw extruder for melt extrusion; set the temperatures of the parallel twin-screw extruder as follows: 160-170°C for zone 1; 180-190°C for zone 2; 200-210°C for zone 3; 220-230°C for zone 4; 230-235°C for zone 5; 230-235°C for zone 6; 230-235°C for zone 7; 210-220°C for zone 8; 210-220°C for zone 9; 190-200°C for zone 10; set a side feeding port in zone 6 to add glass fiber; set a vacuum devolatilization port in zone 8 to exhaust; and obtain a self-cleaning ABS composite modified material for grater through melt extrusion, drawing, air cooling of conveyor chain, roller cutting and screening.
[0022] Preferably, the stirring speed of the vertical stirred mill in step S1 is 120-200rpm; the kinetic energy of grinding is transferred to the grinding medium zirconium balls through the rotation of the stirring shaft, and the zirconium balls impact and grind the materials, so that the nanomaterials are evenly dispersed in the ABS high-rubber powder and further refined. Further preferably, the particle size of the zirconium balls is 1-2mm. Smaller particle sizes are more conducive to the refinement and dispersion of nanomaterials. In order to facilitate the screening of zirconium balls after grinding, it is not recommended to use zirconium balls with a particle size less than 1mm in actual operation.
[0023] Preferably, the side feeding in step S3 is metered according to the number of strands added according to the linear density of the continuous glass fiber when using alkali-free continuous glass fiber; and is metered using a loss-in-weight scale when using alkali-free chopped glass fiber.
[0024] ABS (acrylonitrile-butadiene-styrene copolymer) has been widely used in injection molding graters, and it has excellent physical and chemical properties. However, it is difficult to clean the surface of ABS because water and oil easily adhere to it, and it is easy to breed bacteria due to the adhesion of oil. The present invention modifies ABS, and uses a synergistic formula combination to enhance the strength and rigidity of ABS through glass fiber, and pre-disperses nanomaterials and polytetrafluoroethylene through high-rubber powder to achieve efficient dispersion of nanomaterials in ABS. Nano-SiO2, nano-TiO2, nano-ZnO cooperate with polytetrafluoroethylene and silicone masterbatch to improve the self-cleaning, hydrophobic and oleophobic properties of the surface of the injection molding grater, effectively preventing the adhesion of oil and the breeding of bacteria; at the same time, it improves the aging resistance of the product and prevents ABS from yellowing and discoloration.
[0025] Compared with the prior art, the technical solution of this application has the following outstanding features and beneficial effects: 1. In the present application, precipitated barium sulfate, polytetrafluoroethylene powder, nano-SiO2, nano-TiO2, and nano-ZnO are pre-grinded and dispersed in high-rubber powder, thereby promoting efficient composite dispersion of polytetrafluoroethylene powder and nano-materials in ABS. The surface of the injection-molded ABS product exhibits excellent hydrophobicity and oleophobicity, effectively preventing the adhesion of oil stains and the growth of bacteria, and has a significant self-cleaning effect.
[0026] 2. This application improves the ultraviolet shielding performance of the surface of injection-molded ABS products and prevents aging and discoloration by pre-dispersing nano-TiO2 and nano-ZnO.
[0027] 3. This application uses MBS resin with a high proportion of methyl methacrylate to enhance polarity, promote compatibility of glass fiber, precipitated barium sulfate, polytetrafluoroethylene powder, nano-SiO2, nano-TiO2 and ABS, and enhance the gloss of the material.
[0028] 4. The preparation technology of this application is easy to control, and the equipment used are all conventional equipment, which is easy to scale up production. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to further clarify the technical effects of the present invention, the technical effects of the present invention are compared and explained below with reference to the accompanying drawings: Figure 1 This is a diagram showing the hydrophobic effect of the surface of the injection-molded sample of the self-cleaning ABS composite modified material prepared in Example 1.
[0030] Figure 2 This is a diagram showing the oleophobic effect on the surface of the injection-molded sample of the self-cleaning ABS composite modified material prepared in Example 1.
[0031] Figure 3 This is a diagram showing the hydrophobic effect of the surface of the injection-molded sample of the self-cleaning ABS composite modified material prepared in Comparative Example 1.
[0032] Figure 4 This is a diagram showing the oleophobic effect on the surface of the injection-molded sample of the self-cleaning ABS composite modified material prepared in Comparative Example 1.
[0033] Figure 5 This is a diagram showing the hydrophobic effect of the surface of the injection-molded sample of the self-cleaning ABS composite modified material prepared in Comparative Example 2.
[0034] Figure 6 This is a diagram showing the oleophobic effect on the surface of the self-cleaning ABS composite modified material injection molded sample prepared in Comparative Example 2.
[0035] Figure 7 This is a diagram showing the hydrophobic effect of the surface of the injection-molded sample of the self-cleaning ABS composite modified material prepared in Comparative Example 3.
[0036] Figure 8 This is a diagram showing the oleophobic effect on the surface of the self-cleaning ABS composite modified material injection molded sample prepared in Comparative Example 3.
[0037] Fig. 9 This is a diagram showing the hydrophobic effect of the surface of the injection-molded sample of the self-cleaning ABS composite modified material prepared in Comparative Example 4.
[0038] Fig.10 This is a diagram showing the oleophobic effect on the surface of the self-cleaning ABS composite modified material injection molded sample prepared in Comparative Example 4. DETAILED DESCRIPTION
[0039] In order to enable those skilled in the art to better understand the solution of the present invention, the technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only embodiments of a part of the present invention. Based on the technical ideas of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0040] The raw materials used in the following embodiments of the present invention can be purchased from the market. Unless otherwise specified, they are considered to be conventional raw materials that can be understood by those skilled in the art. The specifications of some raw materials are as follows: ABS resin: brand PA-757F (provided by CHIMEI); ABS high-rubber powder: particle size ≤50μm; butadiene content is 68-70%; MBS resin: coarse powder with a particle size of 20-50 mesh; the mass proportion of methyl methacrylate is 65%; Alkali-free continuous glass fiber: brand 988A, fiber diameter 13μm (provided by China Jushi Co., Ltd.); Gas phase nano-SiO2: particle size is less than 50nm; Precipitated barium sulfate: D50 particle size is 1.5-2μm; Polytetrafluoroethylene powder: The particle size of D50 is 2-10μm; Anatase nano-TiO2; particle size is less than 50nm; Nano ZnO: D50 particle size is 50-100nm. Example 1
[0041] S1. Weigh 6 parts of fine powder raw materials ABS high glue powder, 5 parts of precipitated barium sulfate, 3 parts of polytetrafluoroethylene powder, 3 parts of gas-phase nano-SiO2, 1 part of rutile nano-TiO2, 1 part of nano-ZnO, 0.5 parts of anti-glass fiber exposure agent TAF according to weight, add to the vertical stirred mill, grind with 2mm zirconium oxide balls as the dispersing grinding medium, control the stirring speed to 200rpm, stir for 45min, and impact and grind the material through the zirconium balls, so that the nanomaterials are evenly dispersed in the ABS high glue powder and further refined; then screen out the zirconium balls, add 0.3 parts of antioxidant BHT and 0.5 parts of liquid auxiliary compatibilizer KH-580, mix well, and send to 1# silo for standby; S2. Weigh 60 parts of granular raw materials ABS resin, 8 parts of MBS resin, and 0.3 parts of silicone masterbatch according to weight, add high-speed mixer for high-speed dispersion and mixing, and feed into 2# silo for standby; S3. Use a loss-in-weight scale to automatically weigh and measure the materials in 1# silo and 2# silo, mix the materials, measure 20.3 parts in 1# silo and 68.3 parts in 2# silo, add them into the hopper of parallel twin-screw extruder for melt extrusion; set the temperature of parallel twin-screw extruder as follows: 170℃ in zone 1; 180℃ in zone 2; 200℃ in zone 3; 220℃ in zone 4; -235℃ in zone 5; 235℃ in zone 6; 235℃ in zone 7; 220℃ in zone 8; 210℃ in zone 9; 200℃ in zone 10; set a side feeding port in zone 6 to add continuous glass fiber in an amount of 20 parts; set a vacuum devolatilization port in zone 8 to exhaust; after melt extrusion, drawing, air cooling of conveyor chain, roller cutting and screening, a porcelain white self-cleaning ABS composite modified material for grater is obtained. Example 2
[0042] S1. Weigh 8 parts of fine powder raw materials ABS high glue powder, 5 parts of precipitated barium sulfate, 3 parts of polytetrafluoroethylene powder, 3 parts of gas-phase nano-SiO2, 1 part of rutile nano-TiO2, 1 part of nano-ZnO, 0.5 parts of anti-glass fiber exposure agent EBS according to weight, add vertical stirred mill, grind with 2mm zirconium oxide balls as dispersing grinding medium, control the stirring speed to 120rpm, stir for 60min, and impact and grind the material by zirconium balls, so that the nanomaterials are evenly dispersed in the ABS high glue powder and further refined; then screen out the zirconium balls, add 0.2 parts of antioxidant BHT, 0.1 parts of antioxidant 1076, and 0.5 parts of liquid auxiliary compatibilizer KH-560, mix well, and send to 1# silo for standby; S2. According to the weight of the weighed granular raw material ABS resin 55 parts, MBS resin 8 parts, silicone masterbatch 0.3 parts, light green masterbatch 1 part, add high-speed mixer for high-speed dispersion mixing, sent to 2 # silo standby; S3. Use a loss-in-weight scale to automatically weigh and measure the materials in 1# silo and 2# silo, and mix the materials. 1# silo is measured according to 22.3 parts, and 2# silo is measured according to 64.3 parts. Add them into the hopper of the parallel twin-screw extruder for melt extrusion; the parallel twin-screw extruder is set to the following temperatures: 170℃ for zone 1; 180℃ for zone 2; 200℃ for zone 3; 220℃ for zone 4; -235℃ for zone 5; 235℃ for zone 6; 235℃ for zone 7; 220℃ for zone 8; 210℃ for zone 9; 200℃ for zone 10; set a side feeding port in zone 6 to add continuous glass fiber in an amount of 22 parts; set a vacuum devolatilization port in zone 8 for exhaust; after melt extrusion, drawing, air cooling of conveyor chain, pelletizing by roller cutter, and screening, a light green self-cleaning ABS composite modified material for special grater is obtained. Example 3
[0043] S1. Weigh 8 parts of fine powder raw materials ABS high-rubber powder, 6 parts of precipitated barium sulfate, 4 parts of polytetrafluoroethylene powder, 2 parts of gas-phase nano-SiO2, and 2 parts of anatase nano-TiO2 . 1.5 parts of ABS, 1 part of nano ZnO, 0.5 parts of anti-glass fiber exposure agent TAF, add them into the vertical stirring mill, grind them with 2mm zirconium oxide balls as the dispersing grinding medium, control the stirring speed to 120rpm, stir for 80min, and use the zirconium balls to impact and grind the materials, so that the nano materials are evenly dispersed in the ABS high-rubber powder and further refined; then screen out the zirconium balls, add 0.3 parts of DSTDP and 0.5 parts of liquid auxiliary compatibilizer KH-580, mix them evenly, and send them into the 1# silo for standby use; S2. According to the weight of the weighed granular raw material ABS resin 55 parts, MBS resin 8 parts, silicone masterbatch 0.3 parts, added to a high-speed mixer for high-speed dispersion mixing, sent to 2 # silo standby; S3. Use a loss-in-weight scale to automatically weigh and measure the materials in 1# silo and 2# silo, mix the materials, measure 23.8 parts in 1# silo and 63.3 parts in 2# silo, add them into the hopper of parallel twin-screw extruder for melt extrusion; set the temperature of parallel twin-screw extruder as follows: 170℃ in zone 1; 180℃ in zone 2; 200℃ in zone 3; 220℃ in zone 4; -235℃ in zone 5; 235℃ in zone 6; 235℃ in zone 7; 220℃ in zone 8; 210℃ in zone 9; 200℃ in zone 10; set a side feeding port in zone 6 to add continuous glass fiber in an amount of 22 parts; set a vacuum devolatilization port in zone 8 for exhaust; through melt extrusion, drawing, air cooling of conveyor chain, pelletizing by roller cutter and screening, a self-cleaning ABS composite modified material specially used for porcelain white grater is obtained.
[0044] Comparative Example 1 The implementation scheme is basically the same as Example 1, with the main difference being that the MBS resin is eliminated and replaced with ABS resin.
[0045] Comparative Example 2 The implementation scheme is basically the same as Example 1, with the main difference being that the amount of gas-phase nano-SiO2 used is reduced to 0.5 parts, and the remaining 2.5 parts are replaced by barium sulfate.
[0046] Comparative Example 3 The implementation scheme is basically the same as Example 1, with the main difference being that polytetrafluoroethylene is eliminated and replaced with barium sulfate.
[0047] Comparative Example 4 S1. Weigh 6 parts of fine powdered raw materials ABS high-rubber powder, 5 parts of precipitated barium sulfate, 3 parts of polytetrafluoroethylene powder, 3 parts of gas-phase nano-SiO2, 1 part of anatase nano-TiO2, 1 part of nano-ZnO, 0.5 parts of anti-glass fiber exposure agent TAF, 0.3 parts of antioxidant BHT, 0.5 parts of liquid auxiliary compatibilizer KH-580, mix well, and send to 1# silo for standby;
[0048] S2. Weigh 60 parts of granular raw materials ABS resin, 8 parts of MBS resin, and 0.3 parts of silicone masterbatch according to weight, add high-speed mixer for high-speed dispersion and mixing, and feed into 2# silo for standby; S3. Use a loss-in-weight scale to automatically weigh and measure the materials in 1# silo and 2# silo, mix the materials, measure 20.3 parts in 1# silo and 68.3 parts in 2# silo, add them into the hopper of parallel twin-screw extruder for melt extrusion; set the temperature of parallel twin-screw extruder as follows: 170℃ in zone 1; 180℃ in zone 2; 200℃ in zone 3; 220℃ in zone 4; -235℃ in zone 5; 235℃ in zone 6; 235℃ in zone 7; 220℃ in zone 8; 210℃ in zone 9; 200℃ in zone 10; set a side feeding port in zone 6 to add continuous glass fiber in an amount of 20 parts; set a vacuum devolatilization port in zone 8 to exhaust; after melt extrusion, drawing, air cooling of conveyor chain, roller cutting and screening, a porcelain white self-cleaning ABS composite modified material for grater is obtained.
[0049] The implementation scheme is basically the same as Example 1, with the main difference being that the pre-grinding and dispersion of the nanomaterials is eliminated.
[0050] Performance testing: The performance test was carried out on the ABS modified composite material samples of the above embodiments and comparative examples. In order to prevent the injection molded samples from affecting the judgment, the samples were dried at 80°C for 4 hours before injection molding. The injection molding process was: feed temperature 210°C, compression temperature 220°C, nozzle temperature 200°C, mold temperature 85°C, injection pressure 100kg / cm 2 , pressure maintenance 25kg / cm 2 , back pressure 60MPa.
[0051] 1. Mechanical properties test: Tensile strength test: refer to GB / T 1040.1-2018 and GB / T 1040.2-2006; the sample is dumbbell-shaped, with a thickness and width of 4mm×10mm; the test rate is 20mm / min; the ambient temperature is 23±2℃; the ambient humidity is 50±5%RH. The test results are shown in Table 1.
[0052] Bending performance test: refer to GB / T 9341-2008 test; sample size is 80mm×10mm×4mm; The test speed was 2 mm / min, the ambient temperature was 23 ± 2 °C, and the ambient humidity was 50 ± 5% RH. The test results are shown in Table 1.
[0053] Izod notched impact strength test: refer to GB / T 1843-2008 test; sample size is 80mm×10mm×4mm; nominal energy is 2.75J; ambient temperature is 23±2℃; ambient humidity is 50±5%RH. The test results are shown in Table 1.
[0054] Table 1 Basic mechanical properties test table:
[0055] (II) Self-cleaning performance test: The injection molded sample is a square sample with a thickness of 4mm and a side length of 80mm×80mm. By dropping water and cooking oil on the surface respectively and observing the contact angles of water and oil on the board surface, the self-cleaning effect of hydrophobicity and oleophobicity can be intuitively determined. Figure 1-10 shown.
[0056] Figure 1 , Figure 2 They are respectively the hydrophobic and oleophobic effect diagrams of the surface of the injection molded samples of the self-cleaning ABS composite modified material prepared in Example 1. Through reasonable selection of nanomaterials and pre-grinding and dispersion in high-grade rubber powder in coordination with polytetrafluoroethylene, the size effect of nanomaterials in ABS is obvious, and the hydrophobic and oleophobic properties are significant, which can effectively prevent the adhesion of oil stains and has continuous self-cleaning properties.
[0057] Figure 3 , Figure 4 , respectively, are the hydrophobic and oleophobic effect diagrams of the surface of the injection molded sample of the self-cleaning ABS composite modified material prepared in Comparative Example 1. No MBS resin was added during its preparation, which had a certain impact on the compatibility of the material system and the surface smoothness of the material. The hydrophobic and oleophobic effects are slightly worse, but it still has a good self-cleaning effect.
[0058] Figure 5 , Figure 6 They are respectively the hydrophobic and oleophobic effect diagrams of the surface of the injection-molded samples of the self-cleaning ABS composite modified material prepared in Comparative Example 2. The amount of nano-SiO2 used was greatly reduced during its preparation, and the hydrophobic and oleophobic properties decreased significantly.
[0059] Figure 7 , Figure 8 They are respectively the hydrophobic and oleophobic effect diagrams of the surface of the injection-molded sample of the self-cleaning ABS composite modified material prepared in Comparative Example 3. No polytetrafluoroethylene was used in its preparation, and the hydrophobic and oleophobic properties were significantly reduced.
[0060] Fig. 9 , Fig.10 The hydrophobic and oleophobic effects of the self-cleaning ABS composite modified material injection molded sample prepared in comparative example 4 are shown respectively. The nanomaterials were not ground and pre-dispersed during preparation, and the hydrophobic and oleophobic properties were almost lost. Obviously, efficient dispersion of nanomaterials is extremely critical to exerting the interface and size effects of nanomaterials.
[0061] The above embodiments are only used to illustrate the technical solution of the present application and are not intended to limit it. Although the present application has been described in detail with reference to the preferred embodiments, a person skilled in the art should understand that the technical solution of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present application.
Claims
1. A self-cleaning ABS composite modified material for graters, characterized in that The invention comprises the following raw material components in parts by weight: 50-65 parts of ABS resin, 15-25 parts of glass fiber, 6-8 parts of ABS high-glue powder, 5-8 parts of MBS resin, 5-6 parts of precipitated barium sulfate, 3-4 parts of polytetrafluoroethylene powder, 2-3 parts of nano-SiO2, 1-2 parts of nano-TiO2, 1-2 parts of nano-ZnO, 0.5-1.5 parts of auxiliary compatibilizer, 0.5-0.8 parts of anti-glass fiber exposure agent, 0.3-0.5 parts of silicone masterbatch, 0.3-0.5 parts of antioxidant, and 0-2 parts of masterbatch; The precipitated barium sulfate, polytetrafluoroethylene powder, nano-SiO2, nano-TiO2, nano-ZnO and anti-glass fiber exposure agent are ground and pre-dispersed in ABS high-rubber powder.
2. According to claim 1, a self-cleaning ABS composite modified material for graters is characterized by: The glass fiber is an alkali-free continuous glass fiber or an alkali-free chopped glass fiber pre-impregnated with a silane coupling agent; the fiber diameter is ≤13 μm.
3. The self-cleaning ABS composite modified material for graters according to claim 1 is characterized in that: The particle size of the ABS high-rubber powder is ≤50 μm, and the content of butadiene is 68-70%.
4. The self-cleaning ABS composite modified material for graters according to claim 1 is characterized in that: The particle size of the polytetrafluoroethylene powder D50 is 2-10 μm.
5. The self-cleaning ABS composite modified material for graters according to claim 1 is characterized in that: The particle size of the precipitated barium sulfate D50 is 1.5-2 μm; the nano-SiO2 is gas-phase nano-SiO2; the nano-TiO2 is anatase nano-TiO2; the nano-ZnO is nano-scale ultrafine active ZnO with a particle size of 50-100 nm prepared by wet chemical NPP method.
6. The self-cleaning ABS composite modified material for graters according to claim 1 is characterized in that: The auxiliary compatibilizer is a silane coupling agent.
7. The self-cleaning ABS composite modified material for graters according to claim 1 is characterized in that: The anti-glass fiber exposure agent is selected from ethylene bis fatty acid amide or commercial anti-glass fiber exposure agent TAF.
8. A method for preparing the self-cleaning ABS composite modified material for graters according to any one of claims 1 to 7, the specific method being as follows: S1. Weigh the fine powder raw materials ABS high rubber powder, precipitated barium sulfate, polytetrafluoroethylene powder, nano-SiO2, nano-TiO2, nano-ZnO, and anti-glass fiber exposure agent according to weight, add them to the vertical stirred mill, grind, disperse and refine them with zirconium balls as the dispersing grinding medium; then screen out the zirconium balls, add antioxidants and liquid auxiliary compatibilizers, mix them evenly, and send them to 1# silo for standby use; S2. Weigh the granular raw materials ABS resin, MBS resin, silicone masterbatch, masterbatch according to weight, add high-speed mixer for high-speed dispersion and mixing, and send to 2# silo for standby; S3. Use a loss-in-weight scale to automatically weigh and measure the materials in 1# silo and 2# silo, mix them, and feed them into the hopper of a parallel twin-screw extruder for melt extrusion; set the temperatures of the parallel twin-screw extruder as follows: 160-170°C for zone 1; 180-190°C for zone 2; 200-210°C for zone 3; 220-230°C for zone 4; 230-235°C for zone 5; 230-235°C for zone 6; 230-235°C for zone 7; 210-220°C for zone 8; 210-220°C for zone 9; 190-200°C for zone 10; set a side feeding port in zone 6 to add glass fiber; set a vacuum devolatilization port in zone 8 to exhaust; and obtain a self-cleaning ABS composite modified material for grater through melt extrusion, drawing, air cooling of conveyor chain, roller cutting and screening.
9. The method for preparing the self-cleaning ABS composite modified material for grater according to claim 8, characterized in that: In step S1, the rotation speed of the vertical stirred mill is 120-200 rpm.
10. The method for preparing the self-cleaning ABS composite modified material for grater according to claim 8, characterized in that: The particle size of the zirconium balls in step S1 is 1-2 mm.